Pengembangan Brownies Substitusi Tepung Pisang Modifikasi terhadap Sifat Sensori dan Kandungan Gizi sebagai Salah Satu Alternatif Makanan Tambahan bagi Ibu Hamil: Development of Brownies Substituted with Modified Banana Flour towards Sensory Properties and Nutritional Content as Alternative Supplementary Food for Pregnant Women - Zukryandry, Zukryandry; Vidyarini, Andra; Firdawati, Firdawati; Fitri, Annisa (Universitas Airlangga, 2025)
Background: Regardless of social background, brownies are popular snack among people of all ages, including adults and children. The goal of developing brownies with modified banana flour is to lessen reliance on wheat flour and provide a gluten-free, healthier substitute. More inventive product creation is required because of disparity in sensory qualities of brownie items that are currently on the market. Since starch makes up majority of banana flour, modifying the starch can help to improve the flour's quality. Physical modification is one technique that can be applied to enhance the quality and functionality of banana flour in brownie recipes. Objectives: To determine the sensory properties and nutritional content of brownies with modified banana flour (Musa paradisiaca) substitution. Methods: The research design used a Completely Randomized Design (CRD) with 5 treatments (K=5), 1 experimental unit and 3 repetitions. The treatment carried out was by substituting modified banana flour for wheat flour in brownies products with various different formulations. The resulting brownies products were then analyzed for sensory tests and nutritional content including water content, protein content, fat content, fiber content, ash content, carbohydrates and energy. Results: The results showed that the addition of 80% modified banana flour provided the most preferred sensory properties by respondents in terms of color, aroma, texture, and taste. The nutritional content of 80% modified banana flour substitute brownies including water content, protein content, fat content, fiber content, ash content and carbohydrates were respectively 11.77%; 5.69%; 20.31%; 2.25%; 1.08% and 58.90%. Conclusions: Brownies substituted with modified banana flour have high nutritional content, making it a good choice to meet daily nutritional needs.